Studi Kasus Counterproductive Work Behaviour (Cwb) Karyawan Di Pt X - Ani Supriyani; Sri Muliati Abdullah (Publikasi Indonesia, 2025)
Research on challenges caused by CWB in organizations has been going on for decades. This paper will examine the counterproductive work behavior (CWB) of employees at PT X using a case study approach. The informants in this study include three leaders and three employees at PT X. Data collection techniques using observation, interviews, and documentation. Data analysis uses the research flow from Miles and Huberman. Data validity testing uses observation extension, member check, observation persistence, and triangulation. The findings of the study state that based on the Affective Event Theory (AET) employees who have positive affect experiences and receive positive performance feedback from the company tend to experience positive emotions, such as pride, satisfaction, and have good performance or productivity. Positive emotions experienced by employees are negatively related to the intention to do CWB. The higher the positive emotions experienced by participants, the lower the intention to do CWB. This condition explains how affective experiences affect performance. The dynamics of how to overcome CWB applied by PT X, including; reward and punishment, company as a support system, employee consultation, conducive work climate, challenges to something new, and employee welfare guarantees.